1989
DOI: 10.1259/0007-1285-62-734-121
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of angioplasty balloon catheters: further studies

Abstract: Eight millimetre diameter angioplasty balloon catheters of both the Gruntzig and Olbert types from five manufacturers have been tested in vitro to establish bursting pressures and the changes in maximum and deflated diameters following repeated inflations, both when free and within a restraining sleeve. Maximum inflated diameters were within 10% of that stated and all types of balloon except one burst at a pressure greater than the recommended value. Deflated diameters were approximately 1 mm greater than inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This report provoked two letters reporting similar incidents with the same type of catheter, in one of which the balloon failed to deflate (Raphael & Pardy, 1989;Timmis, 1989). We have previously reported on the behaviour of balloons in angioplasty catheters (Henson et al, 1988;Jeans et al, 1989) and, in view of these newly reported problems, have now carried out tests on a series of catheters to assess the mechanical effects of pulling with varying loads on balloon catheters held at an acute angle.…”
mentioning
confidence: 90%
“…This report provoked two letters reporting similar incidents with the same type of catheter, in one of which the balloon failed to deflate (Raphael & Pardy, 1989;Timmis, 1989). We have previously reported on the behaviour of balloons in angioplasty catheters (Henson et al, 1988;Jeans et al, 1989) and, in view of these newly reported problems, have now carried out tests on a series of catheters to assess the mechanical effects of pulling with varying loads on balloon catheters held at an acute angle.…”
mentioning
confidence: 90%